Rancang Bangun Pedia Pembelajaran Google Colab Untuk Siswa Kelas X SMA Negeri 1 Binjai Berbasis Multimedia Interaktif - Winda Erika; Ania Sahara; Jacky Andre (CV. Hawari, 2024)
The use of multimedia in the world of education is increasing and developing. Creating interactive multimedia-based learning media can provide benefits for teachers to attract students' interest in understanding the material presented. This makes the teaching and learning process more effective and not boring. The Canva application is a platform that is widely used to create interactive multimedia-based learning media. Apart from its attractive design and easy for users to understand, the Canva application is also available for free. There are various types of interesting features that users can easily use to create interactive multimedia-based learning media. Users can create designs in the Canva application according to their desired needs. So that the creation of Google Colab learning media at SMA Negeri 1 Binjai based on interactive multimedia can make it easier for students to understand the material presented by the teacher.